Overtime Histological Changes in the Lungs after Intoxication with Baclofen Alone or in Combination with Ethanol (Experimental Study) - O. L. Romanova; M. L. Blagonravov; P. G. Dzhuvalyakov; V. I. Torshin; A. V. Ershov; E. Kh. Barinov (Общая реаниматология, 2023)
The aim of the study was to evaluate the overtime histological changes in the lungs after intoxication with baclofen alone or in combination with ethanol.Materials and methods. The experiment was carried out on 35 male Wistar rats weighing 290-350 g and aged 20 weeks. The animals were split into 7 equal groups (n=5); test drugs were administered via nasogastric tube: rats from Groups 1, 3 and 5 were treated with baclofen at 85 mg/kg; rats from Groups 2, 4 and 6 received similar dose of baclofen and 40% alcohol by volume at a dose of 7 ml/kg; control group rats were not administered with any drugs. Animals of all groups were removed from the experiment by cervical dislocation under anesthesia (chlorolase) after 3 hours (Groups 1, 2), 4.5 hours (Groups 3, 4) and after 24 hours (Groups 5, 6, and the controls). Lung tissue samples were examined by light microscopy. The nonparametric Kraskel-Wallis test was used for multiple comparisons between the groups, and nonparametric Mann–Whitney test with Bonferroni correction was used for pairwise comparison.Results. Light microscopy showed no pathological changes in the lungs of the Control group animals. Baclofen alone, or in combination with ethanol caused significant circulatory disorders (venular and capillary fullness, hemorrhages in the interalveolar septa (IAS) and alveoli, sludge phenomenon), emphysema, atelectasis and distelectasis, and pulmonary edema. IAS thickness in rats from all experimental groups was different from that in animals from the Control group, all differences confirmed by the Kruskel-Wallis test: H=748, p=0.00001.In Group 1 animals IAS was 44.2% thinner (p=0.00052) vs the control Group, while in all remaining experimental groups it was, on the contrary, thicker: in Group 2 – 57.6% increase in thickness (p=0.000038), in Group 3 – 99 % (p=0.00001), in Group 4 – 2.2-fold increase (p= 0.00001), in Group 5 – 2.1-fold (p= 0.00001), in Group 6 – 2.5-fold increase (p= 0.00001). Most significant increase in IAS thickness (6-fold, p=0.00001) occurred within the period from 3 to 4.5 hours after administration of baclofen, while within the period from 4.5 to 24 hours no statistically significant increase occurred (p=0.99). Co-administration of baclofen and ethanol caused 2.8-fold (p=0.00001) increase in IAS thickness after 3 hours as compared to the effects of baclofen only. IAS thickness at 4.5 hours after baclofen and ethanol co-administration increased by additional 41.8% as compared to thickness at 3 hours (p=0.00001). IAS became 11.8% thicker at 24 hours vs 4.5 hours (p=0.87). At 24 hours IAS was 21.7% (p= 0.0011) thicker after baclofen and ethanol co-administration vs baclofen alone. The alveoli size increased by 69.4% (p=0.00001) in Group 1 animals vs the Control group, by 14.3% (p=0.43) - in Group 2, by 55% (p=0.00004) - in Group 3, by 26.3% (p=0.002) - in Group 4, by 45% (p=0.0003) - in Group 5 (baclofen, 24 h), by 43.3% (p=0.0004) – in Group 6 (baclofen and ethanol, 24 h). Co-administration of baclofen and ethanol initially caused a slight increase in alveoli size, bur 3 hours later there was a visible shrinkage in the diameter of alveoli by 32.5% (p= 0.003) vs baclofen mono, 4.5 hours later – by 18.5% (p= 0.062), and 24 hours later – by 1.2% (p= 0.99), that is, the differences were leveled.Conclusion. The combined effects of baclofen and ethanol induce more severe alterations in pulmonary tissue compared to baclofen alone. The pathological changes in the lungs reached their maximum by 24 hours, which confirmed by morphometric assessment. Morphological changes in pulmonary tissue alongside with established chemical properties of the two agents can be used to diagnose cases of intoxication either with baclofen alone or in combination with ethanol.